STUDY OF SURFACE RUN OFF FLOW CONTROL RIVER OF TANGKA AND MANGOTTONG TO FLOODS SINJAI TOWN SOUTH SULAWESI - (NIM 95006034); Pembimbing: Dr. Ir. M. Syahril B.K. dan Ir. Noortjahyono, Dipl. HE., RAHAYU
Floods in capital of Sinjai regency that occur on June 20th, 2006 form biggest floods in last 15 years period of time. Flood that happen caused by overflow River of Tangka and Mangottong which its flow by pass Sinjai Town. Based on analyze from rainfall data, floods occur caused by Q14 year equal to 1112,34 m3/second at Tangka River and Q25,3 year equal to 346,66 m3/second at Mangottong River. Floods control effort choosen Q25 annual with floods discharge equal to 1,264.88 m3/second at Tangka River and 345,66 m3/second at Mangottong River. There are some proposed alternative of floods controls that is embankment/dyke development, retarding basin and reservoir. Evaluation for alternative proposal of floods control done based on competitive profile matrix, and for hirdolic performance by assist of mathematic model HEC-RAS. Based on that evaluation, retarding basin form better alternative at beginning stage. Retarding basin as alternative I in floods control in town of Sinjai regency have capacity of floods control for reduction floods discharge equal to 512,34 m3/second (40,40%) at Tangka River and 181,71 m3/second (37,90%) at Mangottong River or in other words can reduce floods impact equal to 83,41% at Tangka River and 97,29% at Mangottong River. In further stage, proposed reservoir development (Alternative II), form to effort of better floods control for Sinjai Town. Simulation result represent to that reservoir can reduce floods volume equal to 30.548.556 m3 from floods volume 20.694.294 m3 which must reduced, beside for floods control, reservoir can multipurpose function. Some alternative of floods control which analyzed in this study, expected to give recommendation in floods control effort of Sinjai regency.